Pendampingan UMKM Dalam Analisa Potensi Pengembangan UMKM Melalui Digitalisasi Produk UMKM di Desa Plancungan, Slahung, Ponorogo, Jawa Timur - Devid Frastiawan Amir Sup; Setiawan Bin Lahuri; Imam Kamaluddin; Khoirul Umam; Akhmad Affandi Mahfudz; Robby Fathurrohman; Hujjatul Islam Musthafa Abdurrahman; Faiz Izzatullah; Wildan Hakim; Naufal Azmi Ramadhan; Izzuddien Setiaji; Muhammad Hadi Wijaya Munir; Abdul Jafar; Excel Abu Ramadhan; Muhammad Iqbal Choir; M. Mava Saputra Al Maskuri (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Plancungan village, a small village in Indonesia, has experienced various challenges in developing its Micro, Small, and Medium Enterprises (MSMEs). This article discusses the assistance of digitalization of MSMEs products in Plancungan village which is carried out with the aim of increasing competitiveness and market access for MSMEs. The MSMEs products selected are melons, herbal medicine, tempe, crackers, and pottery. This assistance uses training methods for the use of digital technology, website creation and management, and marketing strategies through social media. The results of this assistance show that MSMEs in Plancungan village have experienced increased sales and wider market exposure. In addition, this digitalization assistance also helps MSMEs to be more adaptive to increasingly dynamic market changes. The recommendation that can be given is to continue to develop digital skills and increase cooperation with related parties in order to expand market reach. With the ongoing collaboration and innovation efforts, it is hoped that MSMEs Plancungan village can continue to grow and become one example of success in facing this digital era, and can be an inspiration for other MSMEs to continue to adapt and develop amidst the increasingly tight competition in this digital era. With the increasing development of technology and digitalization, MSMEs Plancungan village is expected to be able to take advantage of existing opportunities to continue to grow and compete in the global market.